STAFF DEVELOPMENT MANAGEMENT ON A WAY TO STRENGTHEN PERSONNEL POTENTIAL AND THE STATE OF BUSINESS ENTITIES ' ECONOMIC SECURITY - Serhii Kudaktin; Serhii Nazarenko (Фінансово-кредитна діяльність: проблеми теорії та практики, 2023)
The purpose of the study is to conceptualize the principles of staff development management, determine the tasks of this process, factors that reduce the level of employee development efficiency and reasons that minimize the readiness of employees for self-development and professional development. The categorical apparatus of personnel management has been improved by the concepts of «personnel development», and «personnel development management». The connection between the personnel development management and the personnel potential formation of the business entity, capable of providing the enterprise with competitive advantages and continuous activity on the market, is proven. Motives, catalysts, methods and tools of staff development are summarized. It is suggested that at the level of employers and management, staff development should be positioned as a component of the Employee Value Proposition, as well as taken into account when reviewing and updating competency maps. The formation of high-quality information and documentation support for the process of personnel development, in particular, the development of competency maps, IDP plans, and personnel policy, will contribute to increasing the level of efficiency of personnel management of the business entity. Their competent development and compliance at the management level will make it possible to form the personnel potential of the enterprise and ensure a high level of intellectual and personnel security for the company. The consequences that effective management of staff development can have on the state of economic security of business entities are determined. The strategic orientations of personnel development should be organically combined with the organization's strategy, its mission, vision, corporate culture and contribute to the achievement of the goals of existence at optimal time intervals.